A cointegration model of money and wealth - Katrin Assenmacher-Wesche; Andreas Beyer (European Central Bank (ECB), 2020)
Extending the data set used in Beyer (2009) from 2007 to 2017, we estimate I(1) and I(2) money demand models for euro area M3. Wefind that the elasticities in the money demand and the real wealth relations identified previously in Beyer (2009) have remained remarkably stable throughout the extended sample period, once only a few additional deterministic variables in the long run relationships for the period after the start of the global financial crisis and the ECB' s non-standard monetary policy measures are included. Testing for price homogeneity in the I(2) model we find that the nominal-to-real transformation is not rejected for the money relation whereas the wealth relation cannot be expressed in real terms.
Keywords: E41; C32; C22; 330; Money demand; wealth; cointegration; vector error correctionmodel; I(2) analysis